Mechanism of a microscale flat plate heat pipe with extremely high nominal thermal conductivity for cooling high-end smartphone chips. (1st December 2019) - Li, Ji; Lv, Lucang; Zhou, Guohui; Li, Xingping
Graphical abstract: (a) Photo of the microscale FPHP sample, (b) sandwiched structure, (c) cross section, and (d) equivalent thermal conductivity. Highlights: Mechanism of thermal spreading enhancement for a microscale flat plate heat pipe was explored. Nanoscale grooves formed on smooth metal wires contribute to achieving superhydrophilic wick. Quasi-loop-type two phase circulation was verified in the microscale flat plate heat pipe. The microscale flat plate heat pipe has a highest thermal conductivity of 2.88 × 10 4 W/(m⋅K). The microscale flat plate heat pipe can further reduce the temperature of smartphone chips by 10 °C. Abstract: For flat plate heat pipes, under the premise of holding high thermal spreading performance meanwhile being as thin as possible for cooling smartphones, the flow resistance should be minimized and the capillary force be maximized. Firstly, the mechanism of superhydrophilicity in a specially treated wick was explored. Secondly, a visual study on a microscale flat plate heat pipe which can regulate two-phase flow was conducted. The typical two-phase flow patterns were identified in the heating and cooling zones under different heat loads and working orientations. Under the joint action of the above functions, a 500 µm thick flat plate heat pipe was developed and tested under natural air convection and compared with graphite and copper flakes. The results demonstrate that the microscale flat plate heat pipe has a maximum equivalent thermal conductivity up to 2.88 × 10 4 W/(m⋅K), more than 80 times the value of copper and 36 times of graphite, which is superior to any reported thin film heat spreader so far. The proposed microscale flat plate heat pipe is an ideal solution to cool high-end smartphone chips.